Diabetic Foot Care - A Public Health Problem (Journal of Medicine, 2011)
Background: Diabetes is global epidemic with devastating human, social and economic consequences. The disease claims as many lives per year as HIV/AIDS and places a severe burden on healthcare systems and economies everywhere, with the heaviest burden falling on low- and middle-income countries. Despite this, awareness of the global scale of the diabetes threat remains pitifully low, inappropriate diabetic foot care affects, feet health leading to callosities, cracks, fissures, fungal infections, ingrown toe nails and patients end up in ulcers and amputations. Objectives: To assess diabetic patients taking proper foot care according to International Guidelines and its impact on their foot health. Methods: A cross sectional study was conducted at outdoor patients department of Medicine, Liaquat University of Medical Sciences Hospital Hyderabad from 17th January 2008 to 16th January 2009. 100 diabetic patients were selected by non probability convenience sampling according to Performa having questions regarding diabetic foot care derived from American Diabetic Association Guidelines for Diabetic Foot care. Results: Diabetic patients taking proper foot care was only 6%. There were 45(45%) males and 55(55%) females. Mean age was 51.57+10.72 years. 38% patients knew about foot care. 17% used to inspect their feet daily, 20% washed their feet daily, while 73% washed their feet more than once. 23% patients dried their feet after every foot wash, 27% applied emollients, 25% checked shoes before wearing, 24% used to wear correct shoes, 8% used to wear cotton socks and 36% used to walk bare feet. Foot care practices on foot health has statistically highly significant association (p